2019
DOI: 10.1016/j.genhosppsych.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Social inhibition in population-based and cardiac patient samples: Robustness of inhibition, sensitivity and withdrawal as distinct facets

Abstract: Objective: Behavioral inhibition plays a key role in animal stress research and developmental research in children. Therefore, we examined the robustness of our multifaceted model of adult social inhibition that comprises behavioral inhibition, interpersonal sensitivity, and social withdrawal components. Method: A total of 899 adults completed the 15-item Social Inhibition Questionnaire (SIQ15) and measures of emotional distress. Confirmatory Factor Analysis (CFA), reliability estimates, and correlational and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…In 2019, Denollet & Duijndam (2019) proposed a conceptual model of adult social inhibition ( in the online supplemental materials), that included inhibited temperament as a foundation, and encompassed three facets, that is, inhibition in social interaction, sensitivity to social evaluation, and withdrawal and suppressing emotions, respectively, reflecting the behavioral, cognitive, and affective characteristics of social inhibition. This model and its accompanying questionnaire (SIQ15) have been tested in various populations since, showing a confirmation of the three-factor model as a valid construct of adult social inhibition (Duijndam & Denollet, 2019; Treffers et al, 2021). In accordance with the childhood literature on inhibited temperament and behavioral inhibition, adult individuals with social inhibition tend to be at increased risk of internalizing psychopathology, both depression and anxiety (de Moor et al, 2018; Kupper & Denollet, 2014; Treffers et al, 2021).…”
Section: Social Inhibition In Adulthoodmentioning
confidence: 78%
“…In 2019, Denollet & Duijndam (2019) proposed a conceptual model of adult social inhibition ( in the online supplemental materials), that included inhibited temperament as a foundation, and encompassed three facets, that is, inhibition in social interaction, sensitivity to social evaluation, and withdrawal and suppressing emotions, respectively, reflecting the behavioral, cognitive, and affective characteristics of social inhibition. This model and its accompanying questionnaire (SIQ15) have been tested in various populations since, showing a confirmation of the three-factor model as a valid construct of adult social inhibition (Duijndam & Denollet, 2019; Treffers et al, 2021). In accordance with the childhood literature on inhibited temperament and behavioral inhibition, adult individuals with social inhibition tend to be at increased risk of internalizing psychopathology, both depression and anxiety (de Moor et al, 2018; Kupper & Denollet, 2014; Treffers et al, 2021).…”
Section: Social Inhibition In Adulthoodmentioning
confidence: 78%
“…This finding suggests that Type D personality individuals who are characterized by negative affectivity and social inhibition tend to motivationally disengaged in the social‐evaluative stress situation, and such motivational disengagement might in turn elicit physiological disengagement marked by attenuated cardiovascular reactivity to stress. Previous studies have indicated that individuals high on negative affectivity such as neuroticism display less performance motivation (Judge & Ilies, 2002), and individuals high on social inhibition show behaviour withdrawal and emotional disengagement in the social interaction (Duijndam & Denollet, 2019). Type D personality employees are also found to experience less work engagement (van den Tooren & Rutte, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, the results showed that social opportunity was lower among Type D patients. Due to their social inhibition, Type D patients might be less willing to interact with others and perhaps even avoid places where social interaction might occur (Duijndam & Denollet, 2019; Kupper & Denollet, 2014). This inhibition might, however, result in negative health outcomes in a twofold way.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that Type D personality is also related to “dysfunctional” social behavior. Type D personality is characterized by higher behavioral inhibition in social situations and increased social withdrawal (Allen, Handy, Blankenship, & Servatius, 2018; Duijndam & Denollet, 2019) and has been shown to predict lower perceived social support (Michal, Wiltink, Grande, Beutel, & Brähler, 2011) and loneliness (Spek et al, 2018). Other studies showed that Type D is associated with a more maladaptive coping style (Mols & Denollet, 2010; Polman, Borkoles, & Nicholls, 2010), which is also reflected in poor performance and social withdrawal (Borkoles et al, 2018) and increased vulnerability to social (interaction) anxiety (Kupper & Denollet, 2014).…”
mentioning
confidence: 99%